WARDAH’S CUSTOMER SATISFACTION REGARDING PRODUCT PACKAGING INNOVATION, QUALITY AND PRICE: JAKARTA AREA - Putri, Theresia Wongso; Napitupulu, Elfrida Viesta (Jurnal Komunikasi dan Bisnis, 2023)
Many new brands of body and beauty care products have sprung up, we can find almost all varieties from local products and other products that came from other countries. With the fast development of these brands, Wardah needs to be able to take part in "stepping up their game" such as innovating the product packaging, improving product qualities, and adjusting product prices to maintain and increase their customer’s satisfaction. Therefore, the purpose of this study was to determine the effect of product packaging innovation, product quality, and product price on Wardah's customer satisfaction.The sample in this study are consumers of Wardah in the Jakarta area. The data collection method in this study was using questionnaire to collect data, as well as using Google form as tools. Measuring tools used in this study are validity, reliability, arithmetic mean, percentage analysis, scale range, classical assumption test, and multiple regression analysis. The tool used to process and analysed the data is SPSS 20. The results of the study show that product packaging innovation, product quality, and product prices all influence customer satisfaction. In addition, a product’s packaging innovation influences satisfaction with no significant effect, product quality influences customer satisfaction, and price influences customer satisfaction.